(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the process of renewal in the socio-cultural life of the Muslims of Central Asia at the beginning of the twentieth century and the prominent aspects of the Jadid movement. It shows that, although the movement gained strength in the early twentieth century, the social conditions of the mid-nineteenth century gave the impetus to its emergence, and it traces the two main currents within Jadidism – the “isloh” (reform) trend led by Fitrat and Fayzulla Xoʻjaev, and the current led by Abdulvohid Burhonov that sought reform through the “good innovation” (bidʻa hasana) of the Sunna. The article analyses the Jadidsʼ wide international ties, their turn from enlightenment to political struggle, Mahmudxoʻja Behbudiyʼs reformist and legal programme, the congresses and organisations of 1917, and the proclamation of the Turkestan Autonomy, concluding that Jadidism was the first movement in three centuries to attempt the building of national democratic statehood.